2021
DOI: 10.3389/frsus.2021.671979
|View full text |Cite
|
Sign up to set email alerts
|

The Circular Economy Lifecycle Assessment and Visualization Framework: A Case Study of Wind Blade Circularity in Texas

Abstract: Moving the current linear economy toward circularity is expected to have environmental, economic, and social impacts. Various modeling methods, including economic input-output modeling, life cycle assessment, agent-based modeling, and system dynamics, have been used to examine circular supply chains and analyze their impacts. This work describes the newly developed Circular Economy Lifecycle Assessment and Visualization (CELAVI) framework, which is designed to model how the impacts of supply chains might chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Transportation costs and logistical barriers are likely to constrain the diversion of EOL wind blades from landfills (Cooperman et al, 2021;Hanes et al, 2021). The Electric Power Research Institute evaluated transportation costs to be about $0.20/metric ton-mile for a 10-ton load of blade materials (EPRI, 2020), whereas James and Goodrich's (EPRI, 2020; James and Goodrich, 2013) estimation is $14-$22/mile or ll OPEN ACCESS iScience 25, 104734, August 19, 2022 $3.7-$4.4/metric ton-mile for 40-45-meter blades.…”
Section: Increased Recycling Rates In Low Cost Transportation Scenariosmentioning
confidence: 99%
See 3 more Smart Citations
“…Transportation costs and logistical barriers are likely to constrain the diversion of EOL wind blades from landfills (Cooperman et al, 2021;Hanes et al, 2021). The Electric Power Research Institute evaluated transportation costs to be about $0.20/metric ton-mile for a 10-ton load of blade materials (EPRI, 2020), whereas James and Goodrich's (EPRI, 2020; James and Goodrich, 2013) estimation is $14-$22/mile or ll OPEN ACCESS iScience 25, 104734, August 19, 2022 $3.7-$4.4/metric ton-mile for 40-45-meter blades.…”
Section: Increased Recycling Rates In Low Cost Transportation Scenariosmentioning
confidence: 99%
“…The developed ABM assesses the mass of EOL wind blades that avoids being landfilled and the costs and revenues associated with the different design and EOL options. In addition to the behavioral dynamics captured with the TPB, the ABM accounts for technological development dynamics, such as the increase in wind turbines' rated capacity (NREL, 2021) and the learning effect (i.e., the decrease in recycling costs with increasing recycled volumes due to factors such as economies of scale) that are likely to occur in future wind blade recycling (Hanes et al, 2021). The ABM is also spatially resolved whenever possible (e.g., using the wind turbine coordinates contained in the US Wind Turbine Database [USWTDB]).…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moving toward circularity is expected to have positive environmental and economic impacts, but this is not guaranteed to do so. For example, Hanes et al (2021) demonstrated that a specific recycling solution is an economically feasible option, but it requires high energy consumption which results in a 7.1% increase in global warming.…”
Section: Limitations and Future Researchmentioning
confidence: 99%